Identification of two novel and one rare mutation in DYRK1A and prenatal diagnoses in three Chinese families with intellectual Disability-7 - Huang, Cheng; Luo, Haiyan; Zeng, Baitao; Feng, Chuanxin; Chen, Jia; Yuan, Huizhen; Huang, Shuhui; Yang, Bicheng; Zou, Yongyi; Liu, Yanqiu (Frontiers in Genetics, 2023)
Background and purpose: Intellectual disability-7 (MRD7) is a subtype disorder of intellectual disability (MRD) with feeding difficulties, hypoactivity, febrile seizures at an age of early onset. We purposed to identifiy the underlying causative genetic factors of three individuals in each Chinese family presented with symptoms of intellectual disability and facial dysmorphic features. We provided the prenatal diagnosis for the three families and genetic counseling for the prevention of this disease.The probands and their next of kin were executed for investigating the genetic sources by Trio-whole exome sequencing (WES). Technologies for next step as Sanger sequencing or quantitative PCR was then carried out to verify the variants confirmed with Trio-WES for the three pedigrees. Moreover, we performed amniocentesis to explore the state of the three pathogenic variants in the fetuses by prenatal molecular genetic diagnosis at a fit gestational period for the three families.The three probands and one fetus were clinically diagnosed with microcephaly and exhibited intellectual developmental disability, postnatal feeding difficulties and facial dysmorphic features.Combining probands' clinical manifestations, Trio-WES uncovered the three heterozygous variants in DYRK1A: a novel variant exon3_exon4del p.(Gly4_Asn109del), a novel variant c.1159CT p.(Gln387*) and a previously presented but rare pathogenic variant c.1309C  T p. (Arg437*) in three families, respectively. Considering with clinical features and molecular testimony, the three probands were confirmly diagnosed with MRD7. These three discovered variants were considered as the three families'causal mutations for MRD7. Prenatal diagnosis detected the heterozygous dominant variant of c.1159C  T p.(Gln387*) in one of the fetuses, indicating a significant probability of MRD7, subsequently the gestation was intervened by the parents' determination and professional obstetrical operation. On the other side, prenatal molecular genetic testing revealed wild type alleles in the other two fetuses and their parents both decided to sustain the gestation.We identified two novel and one rare mutation in DYRK1A which has broadened the spectrum of DYRK1A and provided evidence for the diagnosis of MRD7 at molecular level. Besides, this study has supported the three families with MRD7 to determine the causative genetic factors efficiently and provide concise genetic counseling for the three families by using Trio-WES technology.